The Family is the National Symbol of the Cradle of Values (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
A person living in a family can become a full-fledged and mature person of this nation only when he has deep knowledge of the history, lifestyle, culture, mentality and spirituality of his nation's national family traditions. A perfect person, in turn, tries to teach the ideas and experiences learned in his family life to the next generation. This teaching is the basis for continuing family and social life. The article focuses on these issues.